2012
DOI: 10.3390/ijms14010108
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Resistance to Endocrine Therapy in Breast Cancer: Focus on Signaling Pathways, miRNAs and Genetically Based Resistance

Abstract: Breast cancer is the most frequent malignancy diagnosed in women. Approximately 70% of breast tumors express the estrogen receptor (ER). Tamoxifen and aromatase inhibitors (AIs) are the most common and effective therapies for patients with ERα-positive breast cancer. Alone or combined with chemotherapy, tamoxifen significantly reduces disease progression and is associated with more favorable impact on survival in patients. Unfortunately, endocrine resistance occurs, either de novo or acquired during the course… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
199
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(203 citation statements)
references
References 247 publications
4
199
0
Order By: Relevance
“…This ERP status greatly affected the clinical efficacy, and even lead to the failure of clinical BC treatment. Recently, certain studies reported that ERP may be associated with the following factors: Certain receptors, such as human epidermal growth factor-2, insulin-like growth factor receptor and fibroblast growth factor receptor, the phosphoinositide 3-kinase-Akt signal pathway and the abnormal expression of associated microRNAs (9)(10)(11)(12)(13)(14)(15). However, these studies did not take the clinical factors into consideration.…”
Section: Introductionmentioning
confidence: 99%
“…This ERP status greatly affected the clinical efficacy, and even lead to the failure of clinical BC treatment. Recently, certain studies reported that ERP may be associated with the following factors: Certain receptors, such as human epidermal growth factor-2, insulin-like growth factor receptor and fibroblast growth factor receptor, the phosphoinositide 3-kinase-Akt signal pathway and the abnormal expression of associated microRNAs (9)(10)(11)(12)(13)(14)(15). However, these studies did not take the clinical factors into consideration.…”
Section: Introductionmentioning
confidence: 99%
“…Potential reasons for endocrine resistance include the following: Loss or modification of ERα expression; ERα mutation; the altered regulation of signaling pathways (phosphoinositide 3-kinase/protein kinase B/mechanistic target of rapamycin and cyclin-dependent kinase 4/6 signaling pathways); cross talk between the ER and growth factor receptor signaling pathways [human epidermal growth factor receptor 2 (HER2)]; altered expression of specific microRNAs; and interactions between the tumor microenvironment and host immune response. Although significant progress has been made in understanding the underlying molecular mechanisms of ligand-independent activation of the ER, the mechanisms of endocrine resistance remain unclear (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…A number of mechanisms, including activation of cell survival, cell stress, and cell signaling pathways, have been proposed as drivers of acquired resistance (6,7 ). Recent deepsequencing studies have highlighted the importance of acquired mutations of the estrogen receptor 1 (ESR1) 6 gene in driving resistance. Key mutation hot spots identified include p.L536, p.Y537, and p.D538, which generate ligand-independent ER␣ transcriptional activity thought to be unresponsive to AIs (8 -12 ).…”
mentioning
confidence: 99%
“…The tumor microenvironment has been suggested as a major factor in conferring innate resistance to cancer therapies (1 ), whereas a large proportion of patients develop resistance while receiving systemic antiestrogens such as tamoxifen or estrogen deprivation therapies such as aromatase inhibitors (AIs) (2)(3)(4)(5). A number of mechanisms, including activation of cell survival, cell stress, and cell signaling pathways, have been proposed as drivers of acquired resistance (6,7 ). Recent deepsequencing studies have highlighted the importance of acquired mutations of the estrogen receptor 1 (ESR1) 6 gene in driving resistance.…”
mentioning
confidence: 99%